Sedimentological, petrographic, and geochemical characterization of Ediacaran platform carbonates (Tamengo Formation, Corumbá Group) - Ramos, Maria Eduarda Alves Ferreira (2019)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Geociências, Programa de Pós-Graduação em Geologia, 2019.